Studies of the Enzymic Capacities and Transport Properties of Pea Root Plastids. - Borchert, S. (1993)
Plastids have been isolated from pea (Pisum sativum L.) roots with a high degree of purity and intactness. In these plastids, the activity of enzymes involved in carbohydrate metabolism have been analyzed and corrected for cytosolic contamination. The results show that fructose-1,6-bisphosphatase, NAD-glyceraldehyde phosphate dehydrogenase, and phosphoglyceromutase are not present in pea root plastids. Transport measurements revealed that inorganic phosphate, dihydroxyacetone phosphate (DHAP), 3-phosphoglycerate, 2-phosphoglycerate, phosphoenolpyruvate, and glucose-6-phosphate (Glc6p) are transported across the envelope in a counterexchange mode. Transport of glucose-1-phosphate was definitely excluded. The oxidation of Glc6P by intact plastids resulted almost exclusively in the formation of DHAP. The parallel measurement of DHAP formation and NO2- consumption during Glc6P-supported nitrite reduction yielded a ratio of NO2-reduced/DHAP formed of 1.6, which is relatively close to the theoretical value of 2.0. These results show that the oxidation of Glc6P, involving the uptake of Glc6P and the release of DHAP, and the reduction of NO2- are very tightly coupled to each other.